The DisputeResolutionof Oil Pollutionby Tan/fer Ship In IndonesianLegal System - Elly Kristiani Purwendah; Marsudi Triatmodjo (Cakrawala Hukum: Majalah Ilmiah Fakultas Hukum Universitas Wijayakusuma, 2015)
The choice of oil pollution dispute resolution by Tanker Ship in national marine law system is highly important to be analyzed in-depth concerning the choice of oil pollution dispute resolution by Tanker Ship in Indonesia is resolved in peaceful manner based on the principle of polluter pays principle. The dispute resolution choice in peace is amended by the internationalinstrument ofUNCLOS in article 279 which is, in Indonesianpositive law system, generated through several national legal  instruments. Furthermore, the  dispute resolution choice is such an important thing considering   the purposes of marine environment protection by the coastal states through the law enforcement of sovereign coastal  states.  The  consequence of  dispute resolutionchoice with the concept of ecocracy and sustainable environmental development, in  line with  the  reconstructive  purpose  of philosophical approach of environmental problem  settlement  through the concept  of ecocracy and the paradigm of deep ecology and green constitution, itis expected to be able to be included in national legal system withe law  enforcers  who  understand  ecoliteracy